PENGARUH DANA PERIMBANGAN, DANA SISA LEBIH PERHITUNGAN ANGGARAN (SILPA) DAN PENDAPATAN ASLI DAERAH TERHADAP BELANJA MODAL DAN DAMPAKNYA PADA PERTUMBUHAN EKONOMI - Sari, Nurmala; Djuanda, Gustian; Sarwani, Sarwani (Economic Faculty, Attahiriyah Islamic University, 2018)
The purpose of this study to determine the effect of equalization funds, the remaining funds over budget calculations and local revenue on capital expenditure and impact on economic growth. The study was conducted by using statistics descriptive method and panel data regression method. The sampling technique used was purposive sampling with a sample of 70 samples. The results in this study showed that’s the balancing fund had no significant effect on capital spending. The remaining budget funds significant effect on capital spending. Local Revenue (PAD) has a significant effect on the capital spending. Equalization funds, fund the remaining budget and revenue together (simultaneously) a significant effect on Capital Expenditure. Capital spending significant effect on economic growth. Keywords: Balance Funds, Fund the remaining budget, Local Revenue, Capital Expenditures, Economic Growth (GDRP)